Proceso de atención nutricional en paciente femenino de 56 años de edad con diabetes mellitus tipo 2 e hipertensión arterial. - Olaya Mosquera, Nataly Noemi (2022)
Type II diabetes mellitus is a disease caused by defects in the action of insulin complicating metabolic decompensations. High blood pressure is a disease that involves a measurement of the force exerted against the walls of the arteries as the heart pumps blood to your body. Suffering from both pathologies requires permanent control of both the person who suffers from it and that of the health service. To avoid long- or short-term complications such as heart problems, kidney atherosclerosis and kidney damage. The nutritional treatment of this clinical case is based on carrying out a process of individualized nutritional care to a 56-year-old female patient with a medical diagnosis of Diabetes Mellitus types II and arterial hypertension, through its objective, which is to improve the nutritional status of the patient diagnosed with type II diabetes mellitus and arterial hypertension through dietary treatment. Its nutritional assessment was evaluated to obtain a comprehensive nutritional diagnosis, a dietary treatment was designed and the treatment was monitored to determine its effectiveness.